AN ANALYSIS RELIABILITY OF GENERATOR SET AS EMERGENCY POWER SUPPLY SUDDENLY OFFS AT PLN ULP BELAWAN - Yahya Koto; Siti Anisah; Solly Aryza (INFOKUM, 2022)
The Generator Set consists of the Engine (Motor Propulsion) and also the Generator / Alternator, as previously explained. This engine uses fuel in the form of Diesel (Diesel Engine) or can also use Gasoline, while the Generator itself is a coil of wire made of copper consisting of a static coil or stator and is also equipped with a rotating coil or rotor. In the process of working, according to physics, the engine rotates the rotor in a generator which then causes a magnetic field in the coil section of the generator. Furthermore, this magnetic field will then interact with the rotor which will then rotate and will produce an electric current which is in accordance with Lorentz's law.